Factors That Affect Deliberation of Maguwoharjo Village Development Planning Sub-District Depok Regency Sleman Yogyakarta - Muhammad Rafi; Ulung Pribadi; Fajar Rahmanto (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2020)
This research is based on the view of the deliberation forum in the village which should be able to provide dialogue space and community involvement as the subject of development planning, however, the facts that are seen are that the community in Maguwoharjo village is still seen as an object of development planning and the essence of the deliberation forum in the public sphere in the village has not been able to reflect in full by the people in the area. This study aims to analyze the factors that influence deliberation in development planning deliberations and analyze points of weakness in the deliberation process in Maguwoharjo village. The method in this study uses qualitative research methods with data analysis techniques using NVivo12plus software. The results showed that the leadership factor had a percentage of around 36% in influencing community involvement, the sociocultural factor in the village had a percentage of around 15% where each figure involved had a dominant view that was very thick with Javanese Culture, from the aspect of communication, had a percentage of around 13% in conveying the interests of village development, then, local political factors have a percentage of around 13%, where every participant involved in the village consultation forum has the same interest in development in his area. This study found that the leadership factor was very dominant in influencing the community to be actively involved in the village discussion forum and still found several weaknesses in the deliberation process in the village.